Analysis of Changes in Nutritional Value During the Process of Making Shredded Tuna fish (Thunus sp) At the Aceh Food Jelly Cooperative - Wahyuni, Sri; Ukhty, Nabila; Akbardiansyah, Akbardiansyah; Fitriani, Fitriani (Universitas Halu Oleo, 2023)
Shredded tuna is one of the products produced by the Aceh Food Fish Jelly cooperative. This product is made through the stages of boiling, grinding, frying and adding additional ingredients. This study aims to determine changes in the nutritional value of shredded tuna (Thunnus sp) during the manufacturing process from raw materials, intermediate products and shredded tuna. This study used an experimental method with research stages consisting of sampling, analysis of nutrient content using the proximate test method consisting of moisture content, ash content, fat content, protein content, crude fiber content and carbohydrate content. The design used was a Completely Randomized Design (CRD) with three different samples, namely fresh tuna meat (F1), tuna meat boiled (F2) and shredded tuna (F3), the test was carried out three times. Data from the test results were analyzed statistically using the ANOVA method and then further tested using Duncan's test. Based on the statistical results, it is known that the processing stages of shredded tuna affect the nutritional content of raw materials, intermediate products, and final products so that H0 is rejected. The results of this study also showed that the water content decreased from raw materials to the final product, while the ash content, fat content, protein content, crude fiber content and carbohydrate content increased from raw materials to the final product. Keywords : Tuna fish, Shredded, Processing, Proximate